Defaultable Debt Pricing in Multi-Factor Models - Lim, Kian Guan (Institutional Knowledge at Singapore Management University, 2002)
This paper employs the structural approach to study defaultable debt pricing under multi-factor models. We extend existing results under the structural approach in two directions. By incorporating multiple factors, we can capture the impact of other economic variables on the debt prices apart from the interest rate factor. In our approach, we provide credit spread pricing using both the real interest rate and inflation rate as state variables. We also extend the analyses to a more general default boundary. In our paper we assume that default happens when the firm value hits a given fraction of the corresponding risk-free debt for the first time. This is also the recovery rate of the defaulted debt. Analytical solutions for both the case of constant recovery rate and the extended case of recovery rate being a deterministic function of time in the multi-factor models are provided in our study. We also provide comparison of the performance of our model with other relevant credit spread models.